Ethnobotanical survey and utilization of medicinal and food plants of Panjgur Balochistan, Pakistan (Asian Journal of Ethnobiology, 2023)
Abstract. Ayoub M, Saeed S, Ahmed A, Ahmed M. 2023. Ethnobotanical survey and utilization of medicinal and food plants of Panjgur Balochistan, Pakistan. Asian J Ethnobiol 6: 26-35. The present study observes the ethnobotanical and ethnopharmacological of indigenous rural communities' knowledge of the Panjgur District of Balochistan, Pakistan. The rural community of Panjgur utilizes different plants as medicine and food, and wild food plants play a secondary role in dietary supplementation. The study aimed to document medicinal plants and traditional herbal medicines used by rural people in the area. Plant specimens were collected, and plant uses were recorded by semi-structured interviews and group discussions of 120 informants, of which 90 were males and 30 were females under different age groups. A total of 63 species were used as medicine or food by local communities. Most species reported were herbs (56%), followed by shrubs (24%). The major preparation mode was fresh use (36%), and leaves were the main parts used. The total use citations for all the plant species used to cure various ailments were reported. The highest use citation for stomachic problems followed by a throat infection, anti-acne, skin allergy, and joint pain. The Use Value (UV) ranged from 0.03 to 3 by Cannabis sativa, followed by Aloe vera, Arundo donax, Chenopodium album, Citrullus colocynthis, Convolvulus arvensis, Prosopis juliflora, Phoenix dactylifera, Lactuca sativa, Ziziphora clinopodioides, and Cestrum nocturnum. This study is the first initiative for ethnobotanical investigation in the Panjgur District of Balochistan. The local community not only uses these medicinal and food plants as food and for herbal treatments but also considers them a source of income. The information generated from this study will also provide a baseline for future investigation to be carried out to evaluate the nutritional and bioactive properties of wild medicinal and food plants.
Keywords: Balochistan, ethnobotany, medicinal plants, Pakistan, Panjgur, wild food plants